Cross-bridged cyclam derivatives with bis(phosphinate) and phosphinate-phosphonate pendant arms (cb-BPC) as chelators for copper radioisotopes - Urbanovský, Peter; David, Tomáš; Hlinová, Veronika; Kubíček, Vojtěch; Pietzsch, Hans-Jürgen; Hermann, Petr (Organic & biomolecular chemistry, 2025)
Copper radioisotopes can be used for imaging as well as for therapy and, thus, can form ideal theranostic pairs. The Cu(II) complexes of cross-bridged cyclam (cb-cyclam) derivatives are considered to be highly stable in vivo. However, the complexes are mostly formed under harsh conditions not compatible with sensitive biomolecules. Here, a new class of cb-cyclam derivatives, cross-bridged bis(phosphinate)cyclams ("cb-BPC"), were investigated. Ligands with one or two methylene-bis(phosphinate) -CH2-PO2H-CH2-PO2H(R) (R = H, OH, substituted alkyl) pendant arms were synthesized. Bifunctionalization on the distant phosphorus atom was carried out by employing P-nitrobenzyl (R = CH2-Ph-4-NO2) precursors and/or, for cb-BPC with two bis(phosphinate) pendant arms, by reactions of silyl-phosphites obtained by silylation of their P(O)-H fragments. The reactive bifunctional groups include amine, carboxylate, azide, isothiocyanate, maleimide and/or tetrazine, and also their orthogonally reactive combination in a single molecule of chelator. The cb-BPCs with one bis(phosphinate) arm were not efficiently radiolabelled with 64Cu. The cb-BPCs with two pendant arms were radiolabelled even at room temperature and with only a small excess of chelator, leading to a high specific activity. Radiolabelling was fully comparable with that of analogous bis(phosphinate) derivatives of cyclam and identical radiolabelling of cyclam and cb-cyclam derivatives was observed for the first time. The cb-BPCs with two bis(phosphinate) pendant arms represent a new class of rigid chelators for copper radioisotopes that are easily synthetically modifiable, highly hydrophilic and radiolabelled under mild conditions.